Understanding French Conversational Implicatures by Foreign Language Study Program Students (Universitas Negeri Semarang, 2023)
Learners of French as a foreign language are expected to be able to use French as French native speakers (bien français). In communication, not all meaning comes from the words spoken. Speeches that contain things like this are called conversational implicatures. Understanding foreign language conversational implicatures is difficult. Learners are required for this ability to be able to communicate like native speakers. The present study intends to know to what extent learners understand conversational implicatures. This study follows Bouton and Pratama's research examining the understanding of conversational implicatures in English as a second language. Respondents of this research were 55 students studying French as a foreign language. In collecting the data, three types of tests were used, namely: (1) a Test of Conversational Implicatures, (2) a Test of Vocabulary Mastery, (3) and Test of Structure Mastery. There are 30 questions about 10 types of conversational implicatures, 30 vocabulary questions, and 30 structure questions. The results of the study revealed that there were 8 questions answered incorrectly by more than 50% of respondents. It also shows that the most difficult types of Conversational Implicature are (a) Indirect Criticism, followed by (b) Quantitative, (c) Qualitative, (d) Manner, and (e) MRR. By using Multiple Linear Regression Analysis, statistically it is revealed that vocabulary and structure mastery contributes to Conversational Implicatures understanding.